Att bo på Rådhusberget. Framtida potential ur befintliga hyresgästers perspektiv - Borefjord, Helene; Wallo, Mikaela (My University, 2013)
Strömstad is a small city located on the Swedish west coast. Urbanization and development is a current issue for the municipally, as for many other in the current situation. The municipal housing company Strömstadsbyggen is one of the parties involved in the extensive development that must be implemented to meet the changes and developments which the issue holds. One area that is of interest in the discussion is Rådhusberget - this due to the existing infrastructure and unique qualities that the area holds. In order to achieve the best solutions possible for the area, Strömstadsbyggen wishes to listen to what the existing tenants at Rådhusberget thinks and feels regarding the area and its future potential. This thesis has therefore been carried out in collaboration with Strömstadsbyggen and has been aimed at identifying the current tenants' thoughts and opinions in the existing area of development and infill potential. The aim of this work was also to investigate how the tenants value their home and local environment in its current state, and what their wishes are for the possible future development of Rådhusberget. To achieve analyzable results concerning how the tenants perceive these aspects, an extensive survey have been carried out which were sent out to all tenants in the area. Additional interviews with residents and staff at Strömstadsbyggen has also been performed. The results obtained through the survey and interviews lay as foundation for the discussion and conclusions presented in this thesis. Furthermore, a set of recommendations and focus areas has been developed which are supported by the results and studied literature. In summation, the survey shows that the respondents generally are content with their current living at Rådhusberget. The result also showed that the respondents prioritize the view from the area highly, as well as the low rent that characterize the area. The majority of the respondents believe that the outdoor environment is one among several important aspects to focus on when it comes to the development of the area, and lastly, eco-friendly accommodation with good opportunities for recycling are desirable amongst the respondents. The final recommendations given to Strömstadsbyggen involve actions for the existing buildings as well as what should be the focus of new, future living. Replacement of existing balconies, improved maintenance and asset management are examples of actions that should be performed on existing buildings. Increase attractiveness and focus on the external environment is included in the recommendations for the future.
Keywords: Samhällsbyggnadsteknik; Building Futures; Civil Engineering; Building Futures